Diseño de un modelo para el monitoreo de personas con problemas de alzheimer basado en las tecnologías GSM / GPRS y GPS - Ñaño Velásquez, Carlos Augusto (2013)
Currently, wireless technology provides much accessibility as GPS_x000D_ receivers, which enables new remote monitoring applications. The flexibility_x000D_ and portability offered by these devices for some applications can be used in_x000D_ places where cables are not appropriate._x000D_ In this paper, making use of new technology satellite positioning and_x000D_ cellular telephony, propose the design of a model based on the GSM / GPRS and_x000D_ GPS, focused to the monitoring of people with Alzheimer's problems._x000D_ To achieve this, has been studied and analyzed how to interact GSM /_x000D_ GPRS and GPS in the monitoring process. The model described as GPS_x000D_ receivers, receive the satellite signal, calculate the position and through red_x000D_ GSM / GPRS is carried out transmission to the server coordinates take care to_x000D_ store in a database for through a web page via the internet can monitor the_x000D_ person with Alzheimer's problems. There is also the possibility that interact_x000D_ from a phone, allowing direct communication with the GPS receiver._x000D_ According to the results the model is reliably obtained due to the correct_x000D_ position of the person suffering from Alzheimer's guaranteeing their safety and_x000D_ tranquility of his family